Xylooligosaccharides obtainable on lignocellulosic residues:alternative for production of functional components of food - Barreto, Andressa Ribas; Zancan, Luiza Rodrigues; Menezes, Cristiano Ragagnin de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The increasing demand for novel foods which are able to promote health and prevent diseases, has attracted worldwide attention on prebiotics. Xylo-oligosaccharides (XOS) are considered one of the few nutraceuticals which can be produced from lignocellulosic biomass. This biomass, in turn, is considered a low cost and waste which often is a systemic problem for the environment. Thus, the production of XOS from agricultural waste offers great opportunities for the food industry as a cheap raw material and available in abundance. The main advantages of the use of XOS, stems from the selective stimulation of the growth of beneficial intestinal microflora include reducing blood glucose levels and blood cholesterol; reduce pro-carcinogenic enzymes in the gastrointestinal tract improving mineral absorption in the large intestine, in addition to stimulating the immune system.Thus, the purpose of this article is to demonstrate the functional effects ofXOS and their getting to from lignocellulosic biomass as an alternative to the formulation of healthy food as well as providing a viable alternative to reduce agricultural waste disposed in the environment.